Eco-Industrial Parks in the Palm Oil Industry: A Systematic Literature Review on Circular Economy and Sustainability Practices - Ivander Adonis Amei; Arifah Arsanti; Ivana Laura Br Sinaga; Leon Gilchrist Paraya; Temmy Wikaningrum; Helmi Maulana (Universitas Islam Sultan Agung, 2025)
As the world's largest palm oil producer, Indonesia has not only a significant economic opportunity but a huge environmental responsibility. Although the palm oil sector constitutes a major sector earning foreign income for the country and providing employment, it generates massive biomass waste. Incorporation of Circular Economy (CE) strategies, such as recover, reuse, recycle, and by-product valorization, provides a potential vehicle to help turn these wastes into renewable energy, organic manures, building materials, and biofuels, with both environmental conservation and long-term economic viability across the supply chain. This study utilizes a Systematic Literature Review (SLR) approach using PRISMA guidelines to synthesize 39 scientific articles from 2020-2025 discussing CE and Eco-Industrial Parks (EIPs) in the palm oil industry in Indonesia. A novelty is the combination of bibliometric mapping with thematic analysis to provide multidimensional synthesis, which discovers three dominant focus areas: (1) Biomass Utilization, (2) Circular Economy Applications, and (3) EIP Conceptualization. CE practices in these dimensions are broadly classified in Table 1 as energy recovery (e.g., biogas from POME), material reuse (e.g., composting EFB, application of POFA in construction), and process optimization (e.g., value chain integration and multi-stakeholder collaboration under EIPs). This study concludes that the structured adoption of CE principles through EIPs can significantly enhance environmental and economic outcomes in Indonesia’s palm oil industry. Future research should focus on quantitative CE indicators and the development of localized EIP models tailored to regional contexts.